2022
DOI: 10.1177/10775587211067315
|View full text |Cite
|
Sign up to set email alerts
|

Societal Costs and Outcomes of Medical and Recreational Marijuana Policies in the United States: A Systematic Review

Abstract: Significant support exists in the United States for legalization of marijuana/cannabis. As of 2021, 36 states and four territories approved the legalization of medical cannabis via medical marijuana laws (MMLs), and 15 states and District of Columbia (DC) have adopted recreational marijuana laws (RMLs). We performed structured and systematic searches of articles published from 2010 through September 2021. We assess the literature pertaining to adolescent marijuana use; opioid use and opioid-related outcomes; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 147 publications
0
4
0
Order By: Relevance
“…Further exacerbating the problem in the USA is the inconsistency of the laws that govern marijuana. It is currently on the controlled substances list, but it is classified for legal use as medical marijuana in 36 states and recreational use in 15 states as well as the District of Columbia ( French et al, 2022 ). Therefore, as the delineation between legally produced hemp and psychoactive forms of Cannabis becomes clearer, and with the passage of more regulations to improve growth conditions, research will undoubtedly provide unprecedented opportunities to expand forensic advances and promote development of industrial and therapeutic possibilities for emblematic Cannabis products.…”
Section: Discussionmentioning
confidence: 99%
“…Further exacerbating the problem in the USA is the inconsistency of the laws that govern marijuana. It is currently on the controlled substances list, but it is classified for legal use as medical marijuana in 36 states and recreational use in 15 states as well as the District of Columbia ( French et al, 2022 ). Therefore, as the delineation between legally produced hemp and psychoactive forms of Cannabis becomes clearer, and with the passage of more regulations to improve growth conditions, research will undoubtedly provide unprecedented opportunities to expand forensic advances and promote development of industrial and therapeutic possibilities for emblematic Cannabis products.…”
Section: Discussionmentioning
confidence: 99%
“…These, for example, include community safety, crime and social cost effects but also the extent to which the elimination of the criminal enforcement and penalties for personal cannabis use and their adverse consequences (e.g., criminal records, educational/employment barriers, social injustice) have impacted on the lives and social welfare of the 5–6 million cannabis users (Callaghan et al, 2021a , 2021b ; Fischer et al, 2020a , 2020b ; Lu et al, 2021 ). Such comprehensive evaluations have yet to be implemented, but may eventually conclude that legalization has been an overall more measured and socially beneficial option for cannabis control in Canada (French et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The association between cannabis policies and adult alcohol use also are unclear. 25 Two studies have found that medical cannabis laws reduced alcohol use, 26 , 27 suggesting that cannabis and alcohol are substitutes. However, 2 other studies found that medical laws increased alcohol use, indicating that the 2 substances were economic complements.…”
Section: Introductionmentioning
confidence: 99%
“…The association between cannabis policies and adult alcohol use also are unclear . Two studies have found that medical cannabis laws reduced alcohol use, suggesting that cannabis and alcohol are substitutes.…”
Section: Introductionmentioning
confidence: 99%